The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1137/080732389
|View full text |Cite
|
Sign up to set email alerts
|

High Order Accurate Methods for the Evaluation of Layer Heat Potentials

Abstract: Abstract. We discuss the numerical evaluation of single and double layer heat potentials in two dimensions on stationary and moving boundaries. One of the principal difficulties in designing high order methods concerns the local behavior of the heat kernel, which is both weakly singular in time and rapidly decaying in space. We show that standard quadrature schemes suffer from a poorly recognized form of inaccuracy, which we refer to as "geometrically induced stiffness," but that rules based on product integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 22 publications
0
46
0
Order By: Relevance
“…It was shown in [11] that Fourier techniques can be used to ameliorate the high computational cost of evaluating the time convolution in thermal layer potentials. An application of this approach is reported in [22]. On the other hand, clustering techniques, which include the fast multipole method, H-matrices, and adaptive cross approximations, have proved to be extremely successful for solving integral formulations elliptic problems with complicated geometries.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in [11] that Fourier techniques can be used to ameliorate the high computational cost of evaluating the time convolution in thermal layer potentials. An application of this approach is reported in [22]. On the other hand, clustering techniques, which include the fast multipole method, H-matrices, and adaptive cross approximations, have proved to be extremely successful for solving integral formulations elliptic problems with complicated geometries.…”
Section: Introductionmentioning
confidence: 99%
“…There is recent work by Li and Greengard in [6,7] on developing fast solvers for the heat equation. Their methods use an integral equation formulation based on the heat kernel and rely on a non-uniform FFT.…”
Section: Introductionmentioning
confidence: 99%
“…Discretization and evaluation of the single layer potential. We first consider the evaluation of the single layer potential, following the treatment of the heat equation in [31,35,53]. There are three fundamental observations to be made.…”
Section: Discretization and Numerical Evaluation Of Layer Potentialsmentioning
confidence: 99%
“…Third, when τ is bounded away from the current time t, as in the history part, then the kernels (and resulting fields) are smooth and admit a variety of simpler approximations. In order to overcome the singular quadrature issues, we design special product integration-based schemes, following the treatment in [53]. In that paper, it is shown that for robustness, it is essential to interchange the order of integration in the layer potentials and to carry out integration in time analytically for polynomial approximations of the layer potential density φ(y, τ ).…”
Section: Discretization and Numerical Evaluation Of Layer Potentialsmentioning
confidence: 99%